High-strength high-degradation magnesium alloy and preparation method thereof
By adding specific elements and process to the magnesium alloy, a high-strength and high-degradation magnesium alloy was prepared, which solved the problem that the mechanical properties and degradation properties of existing magnesium alloys were difficult to improve together, and achieved high-strength and rapid degradation effects, which were suitable for oil and gas mining.
Patent Information
- Application Number
- CN202411735147.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-04
AI Technical Summary
The existing magnesium alloys are difficult to improve synergistically between mechanical properties and degradation properties, and cannot meet the demand for high strength and rapid degradation in oil and gas mining.
High strength and high degradation magnesium alloys containing block Ni-LPSO phase, layered γ' phase and nano β' phase were prepared by adding a specific proportion of rare earth elements Gd and/or Y, transition group elements Ni, Zn and/or grain refinement element Mn to the magnesium alloy, and combining heat treatment and hot extrusion processes.
The tensile strength of magnesium alloy reaches 459-530MPa and the degradation performance is 53.8-104.2mg·cm-2·h-1, meeting the demand for high strength and rapid degradation in oil and gas mining.
Smart Images

Figure CN119753465A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil and gas mining materials, and particularly relates to a high-strength and high-degradation magnesium alloy and a preparation method thereof. Background Art
[0002] In recent years, with the continuous development of my country's economy, the demand for energy such as oil and natural gas has increased. According to statistics from the National Bureau of Statistics, my country's crude oil imports have continued to increase, and its dependence on foreign countries has increased year by year. my country's unconventional oil and gas resources such as shale oil and gas reserves are among the highest in the world, and improving their extraction efficiency plays an important role in increasing my country's oil and gas production capacity.
[0003] Multi-stage fracturing technology is a key technology to improve the efficiency of unconventional oil and gas production. It mainly uses isolation tools to isolate oil and gas wells with different geological structures, and applies different pressures for segmented production, thereby improving the recovery rate of oil and gas wells. Due to the complex underground environment of different oil and gas wells and the different oil and gas depths, higher requirements are placed on the comprehensive performance of fracturing balls and bridge plugs with isolation functions. They not only need to have higher pressure bearing capacity, but also need to degrade quickly after fracturing to form a full-diameter oil outlet channel.
[0004] Magnesium alloy has the characteristics of low density, high specific strength and poor corrosion resistance, so magnesium alloy is the most promising candidate material for the preparation of soluble fracturing tools. However, how to achieve the coordinated regulation of the mechanical and degradation properties of magnesium alloy is a current technical difficulty and requires further research. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the main purpose of the present invention is to provide a high-strength and high-degradation magnesium alloy, aiming to solve the problem that the mechanical properties and degradation properties of existing magnesium alloys are difficult to improve synergistically. The present invention also provides a preparation method and use of the high-strength and high-degradation magnesium alloy.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A high-strength and high-degradation magnesium alloy contains the following components by mass percentage: Gd: 8-20%, Y: 0-5%, Ni: 1.5-2.5%, Zn: 0-1%, Mn: 0-1%, and the atomic ratio of RE (Gd / Y): TM (Ni / Zn) is 1.9-3:1, and the balance is Mg and inevitable impurities.
[0008] In some specific embodiments, the high-strength and high-degradation magnesium alloy includes a bulk Ni-LPSO phase, a layered γ' phase, and a nano-β' phase, and the volume fraction of the bulk Ni-LPSO phase is 30%-40%.
[0009] A method for preparing a high-strength and high-degradation magnesium alloy comprises the following steps:
[0010] 1) Casting: uniformly mixing a nickel source, a magnesium source, a gadolinium source, a yttrium source, and / or a zinc source, and / or a manganese source, and performing smelting and casting to obtain an alloy ingot;
[0011] 2) Heat treatment and hot extrusion: the alloy ingot is subjected to homogenization treatment and extrusion deformation treatment in sequence to obtain an extruded magnesium alloy;
[0012] 3) Aging treatment is performed on the extruded magnesium alloy to obtain a high-strength and high-degradation magnesium alloy.
[0013] In certain specific embodiments, in step (1), during smelting and casting, the temperature is raised to 720-760°C under an inert atmosphere, maintained and stirred to make the composition uniform and the raw materials fully melted. After all the raw materials are melted, the temperature is lowered to 700-720°C and kept at this temperature for 25-30 minutes, and then the alloy ingot is taken out and cooled in a salt bath to obtain an alloy ingot.
[0014] In certain specific embodiments, inert gas protection is used during the smelting and casting.
[0015] In some specific embodiments, the inert gas is selected from at least one of helium, argon, carbon dioxide and sulfur hexafluoride.
[0016] In certain specific embodiments, in step (2), the temperature for homogenization treatment is 480-540°C and the time is 2-12h; the temperature for extrusion deformation treatment is 400-450°C and the extrusion ratio is 9-15. Before extrusion, the alloy ingot after homogenization treatment is kept at the extrusion temperature for 15-45min.
[0017] In certain specific embodiments, the aging treatment in step (3) is performed at a temperature of 200° C. for a time of 0.1-200 h.
[0018] The use of the above-mentioned high-strength and high-degradation magnesium alloy in the preparation of downhole tools for fracturing.
[0019] The aforementioned high-strength and high-degradation magnesium alloy is used in oil and gas production.
[0020] Compared with the prior art, the present invention has at least the following advantages:
[0021] 1) The high-strength and high-degradation magnesium alloy provided by the present invention contains a blocky Ni-LPSO phase, a layered γ' phase and a nano-β' phase, and the volume fraction of the blocky Ni-LPSO phase is 30%-40%. The high-strength and high-degradation magnesium alloy has a tensile strength of 459-530 MPa and a degradation performance of 53.8-104.2 mg·cm -2 ·h -1 .
[0022] 2) The preparation method provided by the present invention is to prepare a block Ni-LPSO phase with a specific proportion, and an alloy with a layered γ' phase and a nano β' phase by adding a specific proportion of rare earth elements Gd and / or Y and transition elements Ni, Zn and / or grain refining element Mn to the magnesium alloy at the same time, and combining a specific process, thereby realizing the preparation of a high-strength and high-degradation magnesium alloy. Specifically, since the potential of the block Ni-LPSO and the layered γ' phase is higher than that of the magnesium matrix, and a micro-galvanic couple is formed with the magnesium matrix, the corrosion of the magnesium alloy is accelerated. In addition, the Ni-LPSO phase as a strengthening phase can significantly improve the mechanical properties of the magnesium alloy, and the layered γ' phase can pin dislocations, inhibit recrystallization and grain growth, and further improve the mechanical properties of the magnesium alloy. In addition, the interaction between the nano-β' phase and the lamellar γ' phase can simultaneously increase the critical shear stress of basal and non-basal slip, significantly improving the mechanical properties of the magnesium alloy; the addition of the Mn element refines the grains, which can improve the mechanical properties of the magnesium alloy through grain boundary strengthening on the one hand, and on the other hand, the grain refinement increases the density of the grain boundaries, and the solute elements segregated at the grain boundaries make the grain boundaries act as cathodes to accelerate the corrosion of the magnesium alloy. In summary, the preparation process of the present invention is simple, and by introducing blocky Ni-LPSO, lamellar γ' phase and nano-β' phase, the strength and degradation performance of the magnesium alloy are synergistically improved, thereby achieving the purpose of high-strength and rapid degradation of the magnesium alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0024] Figure 1 TEM image of the bulk LPSO phase in the aged magnesium alloy provided in Example 1 of the present invention;
[0025] Figure 2 TEM image of the lamellar γ' phase and the nano β' phase in the aged magnesium alloy provided in Example 1 of the present invention;
[0026] Figure 3 The metallographic image of the alloy ingot provided in Example 1 of the present invention after homogenization treatment and heat preservation at 430° C. for 30 minutes;
[0027] Figure 4 The metallographic image of the alloy ingot provided in Example 2 of the present invention after homogenization treatment and heat preservation at 450° C. for 30 minutes;
[0028] Figure 5 The stress-strain diagram of the Mg-Gd-Ni-Zn / Mn alloy provided in Example 1, Example 2 and Example 3 of the present invention;
[0029] Figure 6The metallographic image of the extruded magnesium alloy and the TEM image of the lamellar γ' phase provided in Example 2 of the present invention. DETAILED DESCRIPTION
[0030] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0031] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0032] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0033] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0034] In the following embodiments, the nickel source, magnesium source, gadolinium source, yttrium source, and / or zinc source, and / or manganese source used are pure Mg, pure Zn, Mg-Gd, Mg-Y, Mg-Ni, Mg-Mn intermediate alloys, respectively. Before use, the raw materials are polished to remove the oxide film, cleaned with anhydrous alcohol, and dried for use. Among them, the alloy raw materials pure Mg (99.9wt.%), pure Zn (99.9wt.%), Mg-26.38Gd (wt.%) and Mg-26.18Ni (wt.%), Mg-10Mn (wt.%) were purchased from Jiangxi Shida Magnesium Alloy Technology Co., Ltd.; gas raw materials carbon dioxide (CO2) and sulfur hexafluoride (SF6) were purchased from Chongqing Ruike Gas Co., Ltd.;
[0035] The test methods used in the following embodiments include: tensile test method and corrosion test method
[0036] The mechanical and degradation properties are reflected by testing the main properties of each test sample respectively; the main properties tested in this application include mechanical properties, degradation properties, etc.
[0037] 1) Mechanical properties test;
[0038] The mechanical properties test was carried out using a universal material testing machine (CMT5105) according to the method specified in GB / T16865-2013;
[0039] 2) Degradation performance test
[0040] The degradation performance of the samples was tested using a constant temperature water bath (HH-2) according to the method specified in JB / T7901-1999;
[0041] Example 1
[0042] This embodiment provides a method for preparing a high-strength and high-degradation magnesium alloy, which specifically comprises the following steps:
[0043] (1) Raw material pretreatment: Use pure Mg, pure Zn, Mg-Gd master alloy, and Mg-Ni master alloy, grind them to remove the oxide film, clean them with anhydrous alcohol, and dry them for use.
[0044] (2) Alloy smelting: pre-treated pure Mg, pure Zn, Mg-Gd master alloy, and Mg-Ni master alloy are used as raw materials for batching, and the following components are contained in weight percentage: Gd: 14.8%, Ni: 2%, Zn: 0.46%, and the balance is Mg and unavoidable impurity elements, and the atomic ratio of Gd: (Ni + Zn) is 2.3;
[0045] (3) Smelting in a resistance furnace, using a mixture of SF6 and CO2 as a protective gas during the smelting process, first heating to 760°C and stirring to make the composition uniform and the raw materials fully melted, and then cooling to 720°C and keeping the temperature for 30 minutes after all the raw materials are melted, taking out and cooling in a salt bath to obtain an alloy ingot;
[0046] (4) homogenization treatment: homogenizing the alloy ingot at 520° C. for 4 h to obtain a homogenized magnesium alloy;
[0047] (5) Hot extrusion: The magnesium alloy after homogenization treatment is then kept at 430°C for 30 min, the extrusion temperature is 430°C, the extrusion ratio is 11, and the extrusion is performed once to obtain an extruded magnesium alloy;
[0048] (6) The extruded magnesium alloy is aged at 200°C for 42 hours to obtain an aged magnesium alloy, i.e., a high-strength and high-degradation magnesium alloy.
[0049] The present application conducts morphological analysis on the aged magnesium alloy in this embodiment, wherein the TEM image of the aged magnesium alloy is as follows: Figure 1 and Figure 2 As shown, Figure 1 is the TEM image of the bulk LPSO phase in the aged magnesium alloy. Figure 2 TEM image of the lamellar γ' phase and nano-β' phase in the aged magnesium alloy; Figure 3 This is a metallographic diagram of a magnesium alloy after homogenization treatment and heat preservation at 430°C for 30 minutes; it shows that the high-strength and high-degradation magnesium alloy contains blocky LPSO phase, γ' phase and β' phase.
[0050] The present application tests the mechanical properties and degradation performance of the high-strength and high-degradation magnesium alloy prepared in this embodiment. The results are as follows: Figure 5 The results show that the room temperature tensile strength of the high-strength and high-degradation magnesium alloy is 486 MPa, the yield strength is 361 MPa, and the elongation is 13.1%; and the degradation rate in 93°C, 3wt.% KCl solution is 104.2 mg·cm -2 ·h -1 .
[0051] Example 2
[0052] This embodiment provides a method for preparing a high-strength and high-degradation magnesium alloy, wherein steps (1), (2), (3), (4) and (6) are substantially the same as those in embodiment 1, except that the extrusion process temperature in step (5) is different, specifically:
[0053] Hot extrusion: the magnesium alloy after homogenization treatment is then kept at 450°C for 30 minutes, the extrusion temperature is 450°C, the extrusion ratio is 11, and extrusion is performed once to obtain an extruded magnesium alloy;
[0054] The metallographic image of the alloy ingot in this embodiment after homogenization treatment and heating at 450°C for 30 minutes is shown in the following figure. Figure 4 As shown; and the metallographic phase diagram of the extruded alloy in this embodiment and the TEM diagram of the layered γ' phase are as shown Figure 6 shown.
[0055] The present invention tests the mechanical properties and degradation properties of the high-strength and high-degradation magnesium alloy prepared in this embodiment. The results show that the room temperature tensile strength of the high-strength and high-degradation magnesium alloy is 459 MPa, the yield strength is 342 MPa, and the elongation is 8.5%; and the degradation rate in a 93°C, 3wt.% KCl solution is 70.8 mg·cm -2 ·h -1 .
[0056] Example 3
[0057] This embodiment provides a method for preparing a high-strength and high-degradation magnesium alloy, which specifically comprises the following steps:
[0058] (1) Raw material pretreatment: Use pure Mg, pure Zn, Mg-Gd master alloy, Mg-Mn master alloy, and Mg-Ni master alloy, grind them to remove the oxide film, clean them with anhydrous alcohol, and dry them for use.
[0059] (2) Alloy smelting: pre-treated pure Mg, pure Zn, Mg-Gd master alloy, Mg-Mn master alloy, and Mg-Ni master alloy are used as raw materials for batching, and the following components are contained in weight percentage: Gd: 12.95%, Ni: 2.07%, Zn: 0.42%, Mn: 0.32%, and the balance is Mg and unavoidable impurity elements, and the atomic ratio of Gd: (Ni + Zn) is 1.97;
[0060] (3) Smelting in a resistance furnace, using a mixture of SF6 and CO2 as a protective gas during the smelting process, first heating to 760°C and stirring to make the composition uniform and the raw materials fully melted, and then cooling to 720°C and keeping the temperature for 30 minutes after all the raw materials are melted, taking out and cooling in a salt bath to obtain an alloy ingot;
[0061] (4) homogenization treatment: homogenizing the alloy ingot at 520° C. for 4 h to obtain a homogenized magnesium alloy;
[0062] (5) Hot extrusion: The magnesium alloy after homogenization treatment is then kept at 430°C for 30 min, the extrusion temperature is 430°C, the extrusion ratio is 11, and the extrusion is performed once to obtain an extruded magnesium alloy;
[0063] (6) The extruded magnesium alloy is aged at 200°C for 42 hours to obtain an aged magnesium alloy, i.e., a high-strength and high-degradation magnesium alloy.
[0064] The present invention tests the mechanical properties and degradation properties of the high-strength and high-degradation magnesium alloy prepared in this embodiment. The results show that the room temperature tensile strength of the high-strength and high-degradation magnesium alloy is 475 MPa, the yield strength is 331 MPa, and the elongation is 16.5%; and the degradation rate in a 93°C, 3wt.% KCl solution is 54.7 mg·cm -2 ·h -1 .
[0065] Example 4
[0066] This embodiment provides a method for preparing a high-strength and high-degradation magnesium alloy, which specifically comprises the following steps:
[0067] (1) Raw material pretreatment: Use pure Mg, pure Zn, Mg-Gd master alloy, Mg-Y master alloy, Mg-Ni master alloy, and Mg-Mn master alloy, grind them to remove the oxide film, clean them with anhydrous alcohol, and dry them for use.
[0068] (2) Alloy smelting: pre-treated pure Mg, pure Zn, Mg-Gd master alloy, Mg-Y master alloy, Mg-Ni master alloy, and Mg-Mn master alloy are used as raw materials for batching, and the following components are contained in weight percentage: Gd: 11%, Y: 3%, Ni: 1.9%, Zn: 0.4%, Mn: 0.3%, and the balance is Mg and unavoidable impurity elements, and the atomic ratio of (Gd+Y):(Ni+Zn) is 2.7;
[0069] (3) Smelting in a resistance furnace, using a mixture of SF6 and CO2 as a protective gas during the smelting process, first heating to 760°C and stirring to make the composition uniform and the raw materials fully melted, and then cooling to 720°C and keeping the temperature for 30 minutes after all the raw materials are melted, taking out and cooling in a salt bath to obtain an alloy ingot;
[0070] (4) homogenization treatment: homogenizing the alloy ingot at 520° C. for 12 h to obtain a homogenized magnesium alloy;
[0071] (5) Hot extrusion: The magnesium alloy after homogenization treatment is then kept at 430°C for 30 min, the extrusion temperature is 430°C, the extrusion ratio is 11, and the extrusion is performed once to obtain an extruded magnesium alloy;
[0072] (6) The extruded magnesium alloy is aged at 200°C for 60 hours to obtain an aged magnesium alloy, i.e., a high-strength and high-degradation magnesium alloy.
[0073] The high-strength and high-degradation magnesium alloy prepared in this embodiment is tested for mechanical properties and degradation properties. The results show that the room temperature tensile strength of the high-strength and high-degradation magnesium alloy is 500 MPa, the yield strength is 360 MPa, and the elongation is 5%; and the degradation rate in a 93°C, 3wt.% KCl solution is 54.5 mg·cm -2 ·h -1 .
[0074] Example 5
[0075] This embodiment provides a method for preparing a high-strength and high-degradation magnesium alloy, which specifically comprises the following steps:
[0076] (1) Raw material pretreatment: Use pure Mg, pure Zn, Mg-Gd master alloy, Mg-Y master alloy, Mg-Ni master alloy, and Mg-Mn master alloy, grind them to remove the oxide film, clean them with anhydrous alcohol, and dry them for use.
[0077] (2) Alloy smelting: pre-treated pure Mg, pure Zn, Mg-Gd master alloy, Mg-Y master alloy, Mg-Ni master alloy, and Mg-Mn master alloy are used as raw materials for batching, and the following components are contained in weight percentage: Gd: 8%, Y: 4.5%, Ni: 1.8%, Zn: 0.4%, Mn: 0.3%, and the balance is Mg and unavoidable impurity elements, and the atomic ratio of (Gd+Y):(Ni+Zn) is 2.7;
[0078] (3) Smelting in a resistance furnace, using a mixture of SF6 and CO2 as a protective gas during the smelting process, first heating to 760°C and stirring to make the composition uniform and the raw materials fully melted, and then cooling to 720°C and keeping the temperature for 30 minutes after all the raw materials are melted, taking out and cooling in a salt bath to obtain an alloy ingot;
[0079] (4) homogenization treatment: homogenizing the alloy ingot at 520° C. for 12 h to obtain a homogenized magnesium alloy;
[0080] (5) Hot extrusion: The magnesium alloy after homogenization treatment is then kept at 430°C for 30 min, the extrusion temperature is 430°C, the extrusion ratio is 11, and the extrusion is performed once to obtain an extruded magnesium alloy;
[0081] (6) The extruded magnesium alloy is aged at 200°C for 60 hours to obtain an aged magnesium alloy, i.e., a high-strength and high-degradation magnesium alloy.
[0082] The present application tests the mechanical properties and degradation properties of the high-strength and high-degradation magnesium alloy prepared in this embodiment. The results show that the room temperature tensile strength of the high-strength and high-degradation magnesium alloy is 530 MPa, the yield strength is 370 MPa, and the elongation is 4%; and the degradation rate in a 93°C, 3wt.% KCl solution is 53.8 mg·cm -2 ·h -1 .
[0083] Comparative Example 1
[0084] This comparative example provides a Mg-Gd-Ni-Zn alloy, whose components are basically the same as those in Example 2, except that the content of Gd is the same, but the atomic ratio of Gd:(Ni+Zn) is 1.5: it contains the following components in weight percentage: Gd: 14.8%, Ni: 2%, Zn: 1.7%, and the balance is Mg and unavoidable impurity elements, and its process steps and parameters are the same as those in Example 2.
[0085] In the process of preparing the Mg-Gd-Ni-Zn alloy, the applicant found that there was no obvious aging strengthening effect when the extruded magnesium alloy of the comparative example was subjected to aging treatment; at the same time, the applicant conducted mechanical property and degradation property tests on the Mg-Gd-Ni-Zn alloy prepared in the comparative example, and the results showed that the room temperature tensile strength of the Mg-Gd-Ni-Zn alloy was 420 MPa, the yield strength was 285 MPa, and the elongation was 7.5%; and its degradation rate in 93°C, 3wt.% KCl solution was 100.8 mg·cm -2 ·h -1 .
[0086] Comparative Example 2
[0087] This comparative example provides a Mg-Gd-Ni-Zn alloy, whose components are basically the same as those in Example 2, except that the content of (Ni+Zn) is the same, but the atomic ratio of Gd:(Ni+Zn) is 0.9: it contains the following components in weight percentage: Gd: 6%, Ni: 2%, Zn: 0.46%, and the remainder is Mg and unavoidable impurity elements, and its step parameters are the same as those in Example 2.
[0088] The second phase of the Mg-Gd-Ni-Zn alloy ingot prepared in this comparative example is mainly composed of LPSO phase and a small amount of Mg2Ni phase; the alloy ingot is subjected to homogenization treatment, extrusion and aging treatment at the same time, and it is found that there is no obvious aging strengthening effect.
[0089] The present invention tests the mechanical properties and degradation properties of the Mg-Gd-Ni-Zn alloy prepared in this comparative example. The results show that the room temperature tensile strength of the Mg-Gd-Ni-Zn alloy is 360 MPa, the yield strength is 241 MPa, and the elongation is 6%. The degradation rate in a 93°C, 3 wt.% KCl solution is 68.5 mg·cm -2 ·h -1 .
[0090] Comparative Example 3
[0091] This comparative example provides a Mg-Gd-Ni-Zn alloy, whose composition is basically the same as that of Example 2, except that the content of Gd is the same, but the atomic ratio of Gd:(Ni+Zn) is 3.9: it contains the following components in weight percentage: Gd: 14.8%, Ni: 1%, Zn: 0.46%, and the remainder is Mg and unavoidable impurity elements, and its step parameters are the same as those of Example 2.
[0092] The second phase of the Mg-Gd-Ni-Zn alloy ingot prepared in this comparative example is mainly composed of LPSO phase and a small amount of Mg5Gd type compounds.
[0093] The present invention tests the mechanical properties and degradation properties of the Mg-Gd-Ni-Zn alloy prepared in this comparative example. The results show that the room temperature tensile strength of the Mg-Gd-Ni-Zn alloy is 438 MPa, the yield strength is 298 MPa, and the elongation is 6.5%; and the degradation rate in a 93°C, 3wt.% KCl solution is 32.3 mg·cm -2 ·h -1 .
[0094] Comparative Example 4
[0095] The present comparative example provides a Mg-Gd-Ni-Zn alloy, whose components and proportions are the same as those in Example 2; its process step parameters are basically the same as those in Example 2, except that the alloy ingot is not kept at 450°C for 30 minutes after homogenization treatment (i.e., the alloy ingot after homogenization treatment is not kept at the extrusion temperature before extrusion), specifically: the magnesium alloy after homogenization treatment is extruded at an extrusion temperature of 450°C and an extrusion ratio of 11,
[0096] The present application tests the mechanical properties and degradation properties of the magnesium alloy prepared in this comparative example. The results show that the room temperature tensile strength of the magnesium alloy is 443 MPa, the yield strength is 320 MPa, and the elongation is 8%; and the degradation rate in a 93°C, 3wt.% KCl solution is 62.5 mg·cm -2 ·h -1 .
[0097] Performance Test:
[0098] The present application performs performance tests on the magnesium alloys prepared in Examples 1-5 and Comparative Examples 1-4, wherein the mechanical properties are tested according to GB / T16865-2013, and the degradation rate is tested according to JB / T7901-1999 in a 93°C, 3wt.% KCl solution. The specific results are as follows: Figure 5 As shown in Table 2:
[0099] Table 1 shows the composition phase of the magnesium alloys of various embodiments and comparative examples.
[0100]
[0101] Table 2 Mechanical properties and degradation rates of magnesium alloys of various embodiments and comparative examples
[0102]
[0103] According to the above table, when Gd: 8-20%, Y: 0-5%, Ni: 1.5-2.5%, Zn: 0-1%, Mn: 0-1%, and the atomic ratio of RE (Gd / Y): TM (Ni / Zn) is 1.9-3:1, and combined with the preparation process of the present invention, the prepared magnesium alloy mainly contains blocky Ni-LPSO phase, layered γ' phase and nano β' phase, and the volume fraction of the blocky Ni-LPSO phase is 30%-40%; thereby, the tensile strength of the prepared magnesium alloy is 459-530MPa, the yield strength is 331-370MPa, the elongation is 4-16.5%, and the degradation rate in 93°C, 3wt.% KCl solution is 53.8mg·cm -2 ·h -1 -104.2mg cm -2 ·h -1 .
[0104] At the same time, by comparing Example 2 with Comparative Examples 1-4, it can be seen that when the Gd content is within the range, but the atomic ratio of Gd:(Ni+Zn) is not within the range, such as in Comparative Example 1, the atomic ratio of Gd:(Ni+Zn) is 1.5, due to the increase in Zn content, Zn atoms also participate in the formation of LPSO phase. At this time, the LPSO phase is composed of Mg 12 (GdNi) to Mg 12 (GdNiZn), and the increase in the volume fraction of the LPSO phase also consumes more solute atoms, resulting in no obvious aging strengthening effect on the alloy, and the tensile strength and yield strength of the alloy are reduced from 459MPa and 342MPa to 420MPa and 285MPa, respectively. During the corrosion process, the higher volume fraction of the LPSO phase causes the split magnesium matrix to fall off quickly, and more solute atoms are consumed, which also reduces the density of the rare earth oxide film on the surface of the alloy, so that the corrosion products accumulated on the surface of the alloy are less hindered by the corrosion expansion than in Example 2, so the degradation rate is significantly increased. For example, in Comparative Example 3, the atomic ratio of Gd: (Ni+Zn) is 3.9. Although the solute atoms dissolved in the matrix precipitate and form a high-density nano-β' phase during the aging process, the Ni content is reduced, the volume fraction of the Ni-LPSO phase is reduced, and the excess Gd exists in the form of the Mg5Gd phase, resulting in the tensile strength and yield strength of the alloy being reduced from 459MPa and 342MPa to 438MPa and 298MPa, respectively. During the corrosion process, the reduction of Ni-LPSO phase reduces the volume fraction of the cathode phase, which in turn leads to a significant decrease in the degradation rate of the magnesium alloy.
[0105] When (Ni+Zn) is within the range, but the atomic ratio of Gd:(Ni+Zn) is not within the range, such as in Comparative Example 2, the content of Gd is reduced, and the atomic ratio of Gd:(Ni+Zn) is 0.9. In this comparative example, in addition to the Ni element required to generate the LPSO phase, the excess Ni exists in the form of Mg2Ni phase. Compared with Example 2, the volume fraction of the Ni-LPSO phase is reduced, and the added Gd mainly exists in the form of the LPSO phase, resulting in the alloy having no obvious aging strengthening effect, and the mechanical properties of the magnesium alloy are significantly reduced. The tensile strength and yield strength of the alloy are reduced from 459MPa and 342MPa to 360MPa and 241MPa, respectively. During the corrosion process, the addition of excessive Ni makes it difficult to precipitate the layered γ' phase during the heat treatment after the homogenization treatment, which reduces the volume fraction of the cathode phase, thereby reducing the degradation rate of the magnesium alloy.
[0106] When the alloy components and proportions are the same as those in Example 2, the difference in Comparative Example 4 is that no heat preservation treatment is performed at the extrusion temperature after homogenization treatment, which makes it impossible to precipitate the layered γ' phase in the matrix. This is because when the magnesium alloy after homogenization treatment is subjected to heat preservation treatment, the homogenization treatment of the alloy ingot at high temperature (520℃ / 4h) causes other second phases to be dissolved in the magnesium matrix, and then the low-temperature heat treatment (450℃ / 30min) intensifies the atomic diffusion, and at the same time, the solute atoms are segregated in the stacking fault, thereby forming a layered γ' phase. In addition, the layered γ' phase can pin dislocations, inhibit recrystallization and grain growth during the extrusion process, and improve the mechanical properties of the magnesium alloy. In Comparative Example 4, since the magnesium alloy after homogenization treatment is not subjected to heat preservation heat treatment, the layered γ' phase cannot be precipitated in the matrix, resulting in a decrease in the mechanical properties of the magnesium alloy, and the tensile strength and yield strength of the alloy are reduced from 459MPa and 342MPa to 443MPa and 320MPa, respectively. During the corrosion process, the volume fraction of the cathode phase decreases and the degradation rate of the alloy decreases because the lamellar γ' phase cannot be precipitated.
[0107] In summary, from the perspective of high strength and high degradation, the atomic ratio of RE (Gd / Y): TM (Ni / Zn) is 1.9-3:1, thereby generating a magnesium alloy containing a bulk Ni-LPSO phase, a layered γ' phase, and a nano β' phase with a volume fraction of 30-40%, and its mechanical and degradation properties can be synergistically improved.
[0108] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A high-strength and high-degradation magnesium alloy, characterized in that: It contains the following components in mass percentage: Gd: 8-20%, Y: 0-5%, Ni: 1.5-2.5%, Zn: 0-1%, Mn: 0-1%, and the atomic ratio of RE (Gd / Y): TM (Ni / Zn) is 1.9-3:1, and the balance is Mg and unavoidable impurities.
2. The high-strength and high-degradation magnesium alloy according to claim 1, characterized in that: The high-strength and high-degradation magnesium alloy comprises a block Ni-LPSO phase, a layered γ' phase and a nano β' phase, and the volume fraction of the block Ni-LPSO phase is 30%-40%.
3. The method for preparing a high-strength and high-degradation magnesium alloy according to claim 1 or 2, characterized in that: The steps include: 1) Casting: uniformly mixing a nickel source, a magnesium source, a gadolinium source, and / or a yttrium source, and / or a zinc source, and / or a manganese source, and performing smelting and casting to obtain an alloy ingot; 2) Heat treatment and hot extrusion: the alloy ingot is subjected to homogenization treatment and extrusion deformation treatment in sequence to obtain an extruded magnesium alloy; 3) Aging treatment is performed on the extruded magnesium alloy to obtain a high-strength and high-degradation magnesium alloy.
4. The method for preparing a high-strength and high-degradation magnesium alloy according to claim 3, characterized in that: In step (1), during smelting and casting, the temperature is raised to 720-760°C and kept warm and stirred to make the composition uniform and the raw materials fully melted. After all the raw materials are melted, the temperature is lowered to 700-720°C and kept warm for 25-30 minutes, and then taken out and cooled in a salt bath to obtain an alloy ingot.
5. The method for preparing a high-strength and high-degradation magnesium alloy according to claim 4, characterized in that: Inert gas protection is adopted during the smelting and casting.
6. The method for preparing a high-strength and high-degradation magnesium alloy according to claim 5, characterized in that: The inert gas is selected from at least one of helium, argon, carbon dioxide and sulfur hexafluoride.
7. The method for preparing a high-strength and high-degradation magnesium alloy according to claim 3, characterized in that: In step (2), the temperature for homogenization treatment is 480-540°C and the time is 2-12h; the temperature for extrusion deformation treatment is 400-450°C and the extrusion ratio is 9-15. Before extrusion, the alloy ingot after homogenization treatment is kept at the extrusion temperature for 15-45min.
8. The method for preparing a high-strength and high-degradation magnesium alloy according to claim 7, characterized in that: The temperature of the aging treatment in step (3) is 200° C. and the time is 0.1-200 h.
9. Use of the high-strength and high-degradation magnesium alloy according to claim 1 or 2 in the preparation of downhole tools for fracturing.
10. Use of the high-strength and high-degradation magnesium alloy according to claim 1 or 2 in oil and gas production.